2007
DOI: 10.1063/1.2646436
|View full text |Cite
|
Sign up to set email alerts
|

On the kinetic stability of magnetic structures in electron drift turbulence

Abstract: The generation of large-scale magnetic fields in magnetic electron drift mode turbulence is investigated. The mechanism of magnetic Reynolds stress is elucidated with the help of kinetic theory, and a sufficient criterion in the form of Nyquist's criterion for the generation of zonal magnetic fields is developed. This criterion is then applied to a narrow wave packet, where an amplitude threshold due to finite width of the wave spectrum in k space is found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…This is the reason that zonal flows driven by drift-type turbulence have been intensively investigated theoretically in recent years. [99][100][101][102][103][104][105][106][107][108][109][110][111][112][113] Another reason for the investigation carried out in the given paper are the results obtained by Kaladze et al 86 In that paper it was shown that in EPI plasma three different types of nonlinear solitary vortical structures on the electrostatic drift waves can appear. ͑1͒ Short-scale vortical structures of dipole type stipulated by the vector nonlinearity only.…”
Section: Generation Of Zonal Flows By Electrostatic Drift Waves In Elmentioning
confidence: 78%
“…This is the reason that zonal flows driven by drift-type turbulence have been intensively investigated theoretically in recent years. [99][100][101][102][103][104][105][106][107][108][109][110][111][112][113] Another reason for the investigation carried out in the given paper are the results obtained by Kaladze et al 86 In that paper it was shown that in EPI plasma three different types of nonlinear solitary vortical structures on the electrostatic drift waves can appear. ͑1͒ Short-scale vortical structures of dipole type stipulated by the vector nonlinearity only.…”
Section: Generation Of Zonal Flows By Electrostatic Drift Waves In Elmentioning
confidence: 78%
“…Also, a sufficient criterion for large-scale structure generation was found in the form of Nyquist's criterion in Ref. 24.…”
Section: Introductionmentioning
confidence: 99%